Safety and efficacy of autologous bone marrow clot as a multifunctional bioscaffold for instrumental posterior lumbar fusion: a 1-year follow-up pilot study - Salamanna, Francesca; Tedesco, Giuseppe; Sartori, Maria; Griffoni, Cristiana; Spinnato, Paolo; Romeo, Paolo; Ghermandi, Riccardo; Fini, Milena; Giavaresi, Gianluca; Gasbarrini, Alessandro; Barbanti Brodano, Giovanni (Frontiers in Endocrinology, 2024)
Background: Bone marrow aspirate (BMA), when combined with graft substitutes, has long been introduced as a promising alternative to iliac crest bone graft in spinal fusion. However, the use of BMA is limited by the absence of a standardized procedure, a structural texture and the potential for diffusion away from the implant site. Recently, the potential use of a new formulation of BMA, named BMA clot, has been preclinically described. In this report, we present the results of a prospective pilot clinical study aimed at evaluating the safety and efficacy of autologous vertebral BMA (vBMA) clot as three-dimensional and multifunctional bio-scaffold in instrumented posterior lumbar fusion.Methods: Ten consecutive patients with indication of multi-level (≤5) posterior spinal fusion due to lumbar spine degenerative diseases were included in the study and treated with vBMA. Clinical outcomes were assessed using the Visual Analog Scale (VAS), Oswestry Disability Index (ODI), and EuroQoL-5L (EQ-5L) preoperatively, at 3 months, and at 12 months after spinal fusion. Bone fusion quality was evaluated at the 12-months of follow-up using the Brantigan classification on radiography (XR) imaging. Bone density was measured on computed tomography (CT) scans at 6-and 12-months 2 This is a provisional file, not the final typeset article of follow-up visits at the intervertebral arches and intervertebral joint areas and expressed in Hounsfield Unit (HU).The results indicate a successful posterolateral fusion rate of approximately 100% (considering levels with C, D, and E grades according to the Brantigan classification) at the 12-month follow-up, along with an increase in bone density from 6 to 12 months of follow-up. An improvement in the quality of life and health status following surgery, as assessed by clinical scores (ODI, VAS, and EQ-5L), was also observed as early as 3 months post-surgery. No adverse events related to the vBMA clot were reported.This prospective pilot study demonstrates the effectiveness and safety profile of vBMA clot as advanced bio-scaffold capable of achieving posterior lumbar fusion in the treatment of degenerative spine diseases. This lays the groundwork for a larger randomized clinical study.